THE GREATEST SHOWPENGUIN - Freegard, Lucy (London : Pavilion, 2021)
Poppy's a penguin who's always performed. But now Poppy wants to change her life -- no more juggling, unicycling or breathing fire. She wants to make others happy, but also be happy herself. So she's going to run the show. Can she become The Greatest Showpenguin?
Preschool
Keywords: Penguins -- Juvenile literature; Circus performers -- Juvenile literature; Circus -- Management -- Juvenile literature; Picture books